Diskursus Gender dalam Perspektif Islam : Gender Discourse from an Islamic Perspective - In'am Fuadi Al Idrus (An-Nisa’ Journal of Gender Studies, 2011)
In Indonesia, gender is considered a discourse and a movement that is oriented towards the West, which is why many people, especially those from Islamic boarding schools, are allergic to the term gender. However, if we look closely, long before that, the Quran had revealed the true gender relations in Islam that should exist, only that it did not use the term gender. What is clear is that the Quran discusses the social roles of men and women, including that men and women are equal before Allah (egalitarian), the difference being their level of piety, as stated in (Q.S Al-Hujurat/49: 13); "O mankind, We have created you from a male and a female and made you into nations and tribes, that you may know one another. Verily, the most noble of you in the sight of Allah is the most pious." Historically, gender differentiation has occurred through a very long and diverse process, including because it has been formed, socialized, reinforced, and even constructed socially and culturally, both through the interpretation of religious texts and by the state. This is where the root cause of gender differences being considered the unchangeable nature of God that cannot be changed or exchanged between the two types of beings, thus giving rise to gender inequality for both men and women. Gender differences are not a problem as long as they do not give rise to injustice, but it turns out that the problem is that these gender differences often lead to injustice. If we trace back through history, then gender issues can be studied since pre-Islamic times, the era of the Prophet and his companions, the classical and modern periods. Therefore, this article attempts to discuss the understanding of the meaning of gender from an Islamic perspective. Di Indonesia, gender dianggap sebagai suatu wacana dan sekaligus gerakan yang berkiblat ke Barat, karenanya banyak kalangan terutama dari pesantren yang alergi terhadap istilah gender. Padahal jika dicermati, jauh sebelumnya al-Quran telah mengungkap relasi gender dalam Islam yang sebenarnya dan seharusnya terjadi, hanya saja memang tidak menggunakan istilah gender, tetapi yang jelas al-Quran membincang peran sosial lakilaki dan perempuan, di antaranya bahwa laki-laki dan perempuan dihadapan Allah adalah setara (egaliter), yang membedakan adalah tingkat ketakwaannya, di antaranya sebagaimana (Q.S AlHujurat/49: 13); “Hai manusia, Kami telah menciptakan kamu dari laki-laki dan perempuan dan Kami jadikan kamu berbangsa-bangsa dan bersuku-suku, supaya kamu saling mengenal. Sesungguhnya yang paling mulia di antara kamu di sisi Allah adalah yang paling takwa". Pembedaan gender secara historis terjadi melalui proses yang sangat panjang dan beragam, di antaranya adalah karena dibentuk, disosiulisasikan, diperkuat dan bahkan dikonstruksi secara sosial maupun kultural, baik melalui interpretasi teks-teks keagamaan ataupun oleh negara. Di sinilah sebenarnya akar penyebab utama dianggapnya perbedaan gender sebagai kodrat Tuhan yang tidak bisa dirubah dan dipertukarkan antara kedua jenis mahluk tersebut, sehingga melahirklan ketidakadilan jender (gender inequalities), baik bagi kaum laki-laki maupun perempuan. Perbedaan gender tidak menjadi masalah sepanjang tidak melahirkan ketidakadilan, tetapi ternyata yang menjadi persoalan adalah karena perbedaan gender ini seringkali menimbulkan ketidakadilan. Apabila dirunut dari perjalanan sejarah, maka persoalan gender dapat dikaji sejak pra Islam, masa Nabi dan sahabat, masa klasik dan modern. Oleh karena itu artikel ini mencoba membahas pemahaman makna Gender dalam perspektif Islam.